The Implementation of Tourism Axiological Dimension for Women Survivors: A Philosphical Examination (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
This study aims to analyse the implementation of axiological dimensions of tourism development at Kabupaten Manggarai Barat, especially to women addressed as a victim of gender violence. This research uses a qualitative research method which the key informant comes from representative’s community itself. As a tools of data collection, this study uses field observations, forum group discussion, and literature studies. SWOT Matrix Analysis also uses as data analysing technique. The result of the study showed that there are numbers of strengths, weaknesses, opportunities, and potential threats that interfere the whole implementation of tourism development process and its inclusivity. Therefore, it is recommended that stakeholders need to make a better and strong coordination, then should be followed by common political will, in order to ensure that any strategic-follow-up plans can be implemented properly and efficiently.
Keywords: woman; gender violence; tourism axiological dimension; sustainable tourism; inclusive tourism